Recent development of electrochemically exfoliated graphene and its hybrid conductive inks for printed electronics applications - Suriani binti Abu Bakar, Muhammad Noorazlan Bin Abd Azis (Tanjung Malim, 2024)
Recent development of electrochemically exfoliated graphene and its hybrid conductive inks for printed electronics applications by Suriani binti Abu Bakar, Muhammad Noorazlan Bin Abd Azis